2004
DOI: 10.1128/iai.72.5.2659-2670.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Pneumococcal Disease in Mice Immunized with Conserved Surface-Accessible Proteins

Abstract: The development of a vaccine against Streptococcus pneumoniae has been complicated by the existence of at least 90 antigenically distinct capsular serotypes. Common protein-based vaccines could represent the best strategy to prevent pneumococcal infections, regardless of serotype. In the present study, the immunoscreening of an S. pneumoniae genomic library allowed the identification of a novel immune protein target, BVH-3. We demonstrate that immunization of mice with BVH-3 elicits protective immunity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 32 publications
4
64
0
2
Order By: Relevance
“…Results from antibodylabelling and flow cytometry experiments demonstrated that the Pht proteins are exposed on the surface of the encapsulated bacterium (Hamel et al, 2004), which is in agreement with their relevance as vaccine targets. Based on signature-tagged mutagenesis, it has been suggested that PhtA, PhtB and PhtD are involved in lung-specific virulence (Hava & Camilli, 2002), without further indication about their biological function.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Results from antibodylabelling and flow cytometry experiments demonstrated that the Pht proteins are exposed on the surface of the encapsulated bacterium (Hamel et al, 2004), which is in agreement with their relevance as vaccine targets. Based on signature-tagged mutagenesis, it has been suggested that PhtA, PhtB and PhtD are involved in lung-specific virulence (Hava & Camilli, 2002), without further indication about their biological function.…”
Section: Introductionsupporting
confidence: 63%
“…In a previous study, DNA sequencing of overlapping clones from an S. pneumoniae strain SP64 genomic library (Hamel et al, 2004) and PCR analyses allowed deduction of the genomic organization of the pht genes and their neighbouring genes in this type 6B strain. The phtA and phtB genes, as well as the phtD and phtE genes, were organized as a pair.…”
Section: Characterization Of the Pht Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that one of the two 6B isolates displayed an absence of surface binding could be attributed to the known variation in bacterial capsule thickness or to a lower expression of PhtE, PhtD, and CbpD proteins in this particular strain (38,39). Previous reports have demonstrated that surface-accessible epitopes may elicit antibody-mediated protection against pneumococcal disease (21,40,41), underlining the potential of our epitopes for the development of future vaccines. Additional studies evaluating the in vitro opsonophagocytic and in vivo protective efficacy of anti-peptide antibodies are required.…”
Section: S Pneumoniae Stmentioning
confidence: 99%